IMPLEMENTASI GOOD GOVERNANCE DALAM PENGELOLAAN DANA DESA DENGAN PRESEKTIF SYARIAH DI DESA MLIRIPROWO KECAMATAN TARIK KABUPATEN SIDOARJO - Dianingrum, Silvia (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2018)
The implementation of good governance became a major requirement to realize people aspirations in achieving the regional goals of country. Therefore, it is not excessive when the implementation of good governance became an indication of realization in democratization as an effort to restore the regional sovereignty in a country. In order to realize a better village and able to protect well, the society needed good governance figure. The governance is a hope and an opportunity to realize a prosperous and sovereign life through the management citizensâ€™ freedom and equality. The aim of this research is to know how the implementation of good governance in village funds management with sharia perspective. Based on that background, this research was conducted with the title â€œThe Implementation of Good Governance in Village Fund Management with Sharia Perspective at Mliriprowpo Village Tarik Sub district Sidoarjoâ€. These research used qualitative descriptive method. The location of the research placed at Mliriprowo village Tarik sub district in Sidoarjo. The data sources were obtained from several informants, that is, the village head, the village secretary, the head of general affairs and the head of village financial affairs. The techniques of data collection were interview and documentation. The data analysis used is to describe the properly conditions, analyzed, evaluated, recorded process, and withdrew of conclusion. The result of this research showed that good governance in 2017 based on general perspective in terms of economical, efficient, effective, transparent and accountable as a reference seen from the planned, implemented, administration, reported, accountability, guided and supervised as well as good governance with sharia perspective in terms of shiddiq, amanah, tabliq, and fathonah were already well. However, the governance needed an evaluation, mentoring and guidance in the implementation of development that was not being spread evenly. That evaluation used to resolve the problems which occurred during the execution of development took place.